Effort Decrease Stress Through Education Management Stress in the Adolescent Age Group - Wildan Azka Taslimi; Sari, Niken Yuniar; Ananda, Tiara; Putri Nisa, Maisyaroh; Situmorang, Theressa Dwi Vany; Fitriyanti, Yuliana; Nur, Susfika Mei Sari; Putri, Yuli Amelia; Kurniasih, Wiwik; Rivya, Dian Kahfi; Pramesti, Cindy Iony; Herlina, Herlina (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Stress is a problem that often arise due to an imbalance between demands and abilities, result in physical and psychological disorders. Prolonged stress experienced during adolescence can result in negative impacts such as depression. The aim of this service is to increase the knowledge and abilities of teenagers about stress and stress management among teenage students at Nurul Falah Middle School, Sialangrampai Village, Kulim, Pekanbaru City, Riau. The method used was lecture explanations, questions and answers and demonstrations given by the presenters to Nurul Falah Middle School students. US a result of this activity, it was found that there was a significant increase in knowledge, with the aver age participant understanding score increasing from 40 to 80. From these results, it can be concluded that health education is effective in increasing teenagers' knowledge regarding stress and how to manage stress in teenagers.